Caledonian eclogite-facies metamorphism of Early Proterozoic Protoliths from the North-East Greenland Eclogite Province - Brueckner, H. K.; Gilotti, J. A.; Nutman, A. P. (Contributions to Mineralogy and Petrology, 1998)
High-pressure metamorphic assemblages occur in mafic, ultramafic and a few intermediate rocks in a gneiss complex that covers an area of approximately 400 × 100 km in the North-East Greenland Caledonides. Detailed petrologic and geochronologic studies were carried out on three samples in order to clarify the P-T-t evolution of this eclogite province. Geothermobarometry yields temperature estimates of 700–800 °C and pressure estimates of at least 1.5 GPa from an eclogite sensu stricto and as high as 2.35 GPa for a garnet websterite. The eclogite defines a garnet-clinopyroxene-amphibole-whole rock Sm-Nd isochron age of 405 ± 24 Ma (MSWD 0.9). Isofacial garnet websterites define garnet-clinopyroxene-orthopyroxene-amphibole-whole rock-(biotite) ages of 439 ± 8 Ma (MSWD =2.1) for a coarse-grained sample and 370 ± 12 Ma (MSWD=0.6) for a finer-grained variety. Overgrowths on zircons from the fine-grained pyroxenite and the eclogite give a pooled 206Pb/238U SHRIMP age of 377 ± 7 Ma (n=4). Significantly younger Rb-Sr biotite ages of 357 ± 8, 330 ± 6 and 326 ± 6 agree with young Rb-Sr, K-Ar and 40Ar/39Ar mineral ages from the gneiss complex and indicate slow cooling of the eclogitic rocks. High-pressure metamorphism may have been at least 439 Ma old (Siluro-Ordovician) with cooling through amphibolite-facies conditions in the Devonian and continued crustal thinning and exhumation well into the Carboniferous. Sm-Nd whole rock model ages indicate the eclogite protoliths are Early Proterozoic in age, while 207Pb/206Pb SHRIMP ages of 1889 ± 18 and 1981 ± 8 from anhedral zircon cores probably reflect Proterozoic metasomatism. The samples have negative ɛNd values (−5 to −16) and elevated 87Sr/86Sr ratios (0.708–0.715), consistent with field evidence that the eclogite protoliths were an integral part of the continental crust long before Caledonian metamorphism. The presence of a large Caledonian eclogite terrane in Greenland requires modification of current tectonic models that postulate subduction of Baltica beneath Laurentia during the Caledonian orogeny.
Keywords: geology